A Role for Tocopherol Biosynthesis in Arabidopsis Basal Immunity to Bacterial Infection. Issue 3 (12th September 2019) - Stahl, Elia; Hartmann, Michael; Scholten, Nicola; Zeier, Jürgen
Abstract : Tocopherol biosynthesis is required for effective basal resistance of Arabidopsis to Pseudomonas syringae infection. Abstract: Tocopherols are lipid-soluble antioxidants synthesized in plastids of plants and other photosynthetic organisms. The four known tocopherols, α-, β-, γ-, and δ-tocopherol, differ in number and position of methyl groups on their chromanol head group. In unstressed Arabidopsis ( Arabidopsis thaliana ) leaves, α-tocopherol constitutes the main tocopherol form, whereas seeds predominantly contain γ-tocopherol. Here, we show that inoculation of Arabidopsis leaves with the bacterial pathogen Pseudomonas syringae induces the expression of genes involved in early steps of tocopherol biosynthesis and triggers strong accumulation of γ-tocopherol, moderate production of δ-tocopherol, and generation of the benzoquinol precursors of tocopherols. The pathogen-inducible biosynthesis of tocopherols is promoted by the immune regulators ENHANCED DISEASE SUSCEPTIBILITY1 and PHYTOALEXIN-DEFICIENT4. In addition, tocopherols accumulate in response to bacterial flagellin and reactive oxygen species. By quantifying tocopherol forms in inoculated wild-type plants and biosynthetic pathway mutants, we provide biochemical insights into the pathogen-inducible tocopherol pathway. Notably, vitamin E deficient2 ( vte2 ) mutant plants, which are compromised in both tocopherol and benzoquinol precursor accumulation, exhibit increased susceptibility toward compatible P. syringae and possess heightened levels of markers of lipid peroxidation after bacterial infection. The deficiency of triunsaturated fatty acids in vte2-1 fatty acid desaturase3-2 ( fad3-2 ) fad7-2 fad8 quadruple mutants prevents increased lipid peroxidation in the vte2 background and restores pathogen resistance to wild-type levels. Therefore, the tocopherol biosynthetic pathway positively influences salicylic acid accumulation and guarantees effective basal resistance of Arabidopsis against compatible P. syringae, possibly by protecting leaves from the pathogen-induced oxidation of trienoic fatty acid-containing lipids.